Lingual Kinematics in Dysarthric and Nondysarthric Speakers with Parkinson's Disease - Min Ney Wong; Bruce E. Murdoch; Brooke-Mai Whelan (Parkinson's Disease)
Articulatory dysfunction is recognised as a major contributor to the speech disturbances seen in Parkinson's disease (PD). The present study aimed to compare lingual kinematics during consonant production within a sentence in eight dysarthric (DPD) and seven nondysarthric (NDPD) speakers with PD with those of eleven nonneurologically impaired normal participants. The tongue tip and tongue back movements of the participants during sentence production were recorded using electromagnetic articulography (EMA). Results showed that both the DPD and NDPD had deviant articulatory movement during consonant production that resulted in longer duration of consonant production. When compared with the NDPD group, the DPD group primarily exhibited increased range of lingual movement and compatible duration of production with an accompanying increase in maximum velocity, maximum acceleration, and maximum deceleration. These findings are contrary to proposed theories that suggest articulatory imprecision in dysarthric speakers with PD is the outcome of reduced range of articulatory movement.